TRUNK ROTATION TRAINING FOR IMPROVING WEIGHT TRANSMISSION THROUGH HEMIPLEGIC LOWER EXTREMITY. - ARUNACHALAMM R,; JANANI R,; KUMARESAN A,; KIRUTHIKA, (International Journal of Pharma and Bio Sciences, 2016)
This study evaluated the effectiveness of trunk rotation training in improving weight transmission through hemiplegic lower limb. In this study 30 subjects were randomly assigned into two group namely conventional group and experimental group with six subjects in each group. Subjects in the conventional group received conventional set of exercises, experimental group received all the interventions that were used in conventional group but, Trunk rotation training was additionally given without increasing the treatment duration. All the subjects received 3 weeks of treatment with 5 days of treatment in every week, with one session that lasted 45 minutes per day. The ability of weight shift in standing, in both groups, was measured using a bathroom scale inserted in a wooden platform to standardise the inter limb distance and to prevent movement of the bathroom scales. The analysis of the pre and post intervention values showed that there was a significantly more improvement in the weight transmission in the experimental group. Thus, this study concludes that trunk rotation training is an effective tool in improving weight transmission through the paretic lower extremity in hemiplegic subjects.